Development of standardized mathematics achievement test instruments for measuring senior secondary school students’ learning outcomes - Ibrahim, Bashir Mohammed; Sani, Mohammad Ibrahim; Abdallah, Ibrahim Maryam (S&Co Publishing, 2025)
This study developed a Standardized Mathematics Achievement Test (SMAT) instrument for measuring senior secondary school students’ learning outcomes in Dala education directorate, Kano State, Nigeria. The study adopted an instrumentation design. Three research questions were raised to guide the study. The population of the study comprised all 6,462 SS 3 students of the Dala education directorate. The sample size of the study was 132 SS 3 students drawn from the target population in 7 schools with a total number of 248 students using purposive sampling. Fifty multiple-choice items of the SMAT was developed by the researchers. The content validity of the SMAT was determined using a table of specifications. The reliability of the instrument was calculated using Kuder-Richardson formula 20 (KR-20). The result indicated that the content validity as presented in the table of specification of the SMAT items covered the six main sections of the Mathematics scheme. The result indicated that the internal consistency index of the SMAT was found to be a highly reliable instrument with a reliability coefficient of 0.79. The result also indicated that the difficulty index (DifI) of the SMAT items is moderately difficult, and the discriminatory power indicated that the test items distinguish between intelligent and weaker students. The study recommended that mathematics teachers and researchers should always determine the difficulty and discrimination indices of the test items before using such instruments as a tool for measuring students’ learning outcomes.